La influencia a nivel psicológico y motivacional en la preparación de atletas dedicados al fisicoculturismo (2022)
Bodybuilding is a sport that has been practiced since ancient times and as a physical activity its objectives are to develop, control and define the muscles in the body. Therefore, this research raised as a general objectiv e to determine the influence on the psychological part and in the particular the motivational in the preparation of athletes dedicated to bodybuilding. For this, the case study methodology was used, collecting the data through indepth interviews, finding that the participants know little about the history of this sport. that motivation is essential for the preparation of the sport of bodybuilding and that psychological preparation optimizes the execution and the mental keywords: , Bodybuilding, emotional factor in athletes dedicat h istory, m ed to bodybuilding